Optimizing the Health System Through Increasing Health Service Guarantees in the Context of Fulfilling Human Rights Post the Covid-19 Pandemic in Indonesia - Sahat Maruli Tua Situmeang; Diah Pudjiastuti (Universitas Negeri Semarang, 2023)
The COVID-19 pandemic has had a major impact, especially in the health sector. Health facilities and personnel play a key role in handling this pandemic. The importance of improving the quality of health services does not only depend on regulations, but also structure and culture as an interconnected system. This pandemic has been an important lesson, highlighting the readiness and quality of health services. Community resilience emphasizes the need for health protection as a state responsibility and a constitutional right of citizens. In facing the future, the role of the state, regulations and systems will be crucial in managing the health of its citizens in a sustainable manner. Using normative juridical research methods, the results of the analysis show that the state has full authority through the formation of regulations, infrastructure, improving the quality of human resources, and regulating the health system. This step aims to increase guarantees of public health services and fulfill citizens' human rights in the future.